Self-portrait of the children at a shelter home: struggles within hopes and self-expectation - Mohd Munir, Nur Syuhada; Rais, Haniza (2020)
Neglect, abuse and violence in families lead to children being referred to shelter homes for temporary custody. Regardless the age at admission, the children usually can stay at the shelter until they reach 18 years old. The national statistics shows that the number of children in need of custody and protection has increased from 4,295 in 2014 to 4,453 in 2015 (Children Statistic, 2016). Being away from home, with no parents looking after them, the children have no choice but to manage themselves independently. Despite not having parental guidance, the children still have to go through the normal phases of growing up as teenagers. A qualititave study was conducted with six participants aged 12 to 16 who attended a series of group counseling. All of them attend schools in the neighboring area. The study explored their experiences of growing up at the shelter without parental guidance, and their coping responses when faced with difficulties. This paper focuses on the participants’ self-portrait activity. The outcomes from the self-portrait activity revealed the participants’ true selves, their struggles, hopes and expectations in life.